2015
DOI: 10.1159/000430176
|View full text |Cite
|
Sign up to set email alerts
|

Could MicroRNAs be Regulators of Gout Pathogenesis?

Abstract: MicroRNAs (miRNAs) are a class of noncoding RNAs that mainly negatively regulate gene expression. miRNAs have important roles in many diseases, including inflammatory diseases. Gout is a common arthritis caused by deposition of monosodium urate crystals within joints. Recent studies suggested that miRNAs may be involved in the development of inflammatory arthritis, including acute gouty arthritis. In the present review, we systemically discuss relevant publications in order to provide a better understanding on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 64 publications
0
14
0
2
Order By: Relevance
“…Recently, studies confirmed that miRNAs could regulate IL-1β expression in several ways, thereby affecting inflammatory responses of the body [ 25 27 ]. Also, recent research indicates that miRNAs are involved in the development of inflammatory arthritis, including GA [ 8 , 9 , 28 ]. However, according to current literature, no miRNAs have been identified as directly targeting IL-1β.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, studies confirmed that miRNAs could regulate IL-1β expression in several ways, thereby affecting inflammatory responses of the body [ 25 27 ]. Also, recent research indicates that miRNAs are involved in the development of inflammatory arthritis, including GA [ 8 , 9 , 28 ]. However, according to current literature, no miRNAs have been identified as directly targeting IL-1β.…”
Section: Discussionmentioning
confidence: 99%
“…The adhesion of neutrophils to vascular cells, translocation across endothelial cells, and migration toward inflammatory sites is a basic feature of acute inflammation. 7 Translocation of inflammatory cells across the membrane requires intercellular adhesion molecule 1 (ICAM1).…”
mentioning
confidence: 99%
“…The uptake of MSU crystals by residual macrophages in inflamed tissue stimulates a series of inflammatory pathways that lead to the local recruitment of leukocytes (chemotaxis), possibly through endothelial activation [68]. Although the involvement of TLRs, NLRP3 inflammasome, and IL-1β in the MSU-induced inflammatory reaction is well-known, there are no miRNAs discovered, thus far, directly targeting TLRs, IL-1β, chemokines, and NLRP3 in gout [69]. …”
Section: Oa and Gouty Arthritis: Overview Of Pathophysiological Fementioning
confidence: 99%